2000
DOI: 10.1111/j.1095-8339.2000.tb00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and evolutionary implications of intraspecific variability in chromosome numbers of species of Leucaena Benth. (Leguminosae)

Abstract: Chromosome numbers were determined in 52 individuals of 14 taxa of'&ucaena Benth. from 22 populations. For I,. cu.rpidata and L. lempirana these are the first published chromosome counts. Intraspecific variability was found for L. lmpirana, L. macrophylla and L. shanonii, and one diploid population of the tetraploid species L. pallida was identified. Comparison of our data with those in the literature showed that for L. collinsii and L. macroptylla thrre is a relationship between chromosome number and subspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…There is clear evidence to suggest that interspecific hybridization has been important in Leucaena. Five tetraploid species have been documented (25), and there is preliminary evidence that two of these, L. leucocephala and L. confertiflora, are allopolyploids (26). Artificial crossing experiments have shown that crossability among species is high (27).…”
mentioning
confidence: 99%
“…There is clear evidence to suggest that interspecific hybridization has been important in Leucaena. Five tetraploid species have been documented (25), and there is preliminary evidence that two of these, L. leucocephala and L. confertiflora, are allopolyploids (26). Artificial crossing experiments have shown that crossability among species is high (27).…”
mentioning
confidence: 99%
“…(2n = 26, 52) and in I. cayennensis (2n = 26, 104) (from neighboring forest fragments) suggest that polyploidy is the main mechanism of karyotypic evolution in the genus Inga. In this genus, as well as in several others from the tribes Ingeae (Atchison, 1951;Turner and Fearing, 1960), Acacieae (Oballa and Olng'Otie, 1993), and Mimoseae (Cardoso et al, 2000;Schiffino-Withman, 2004), chromosome numbers that are multiples of 13 are more frequent -with the notable exception of the genus Calliandra, which has x = 8 (Atchison, 1948;Arce, 1992). Interestingly, in I. cayenensis, the diploid cytotype showed interphase nuclei distinct from octaploid, suggesting that structural changes occurred in the latter.…”
Section: Discussionmentioning
confidence: 63%
“…Intraspecific polyploidy is a relatively rare phenomenon in Leguminosae-Mimosoideae, having been reported for some populations of Leucaena palida and L. tricandra of the tribe Mimoseae (Cardoso et al, 2000;Schifino-Wittmann, 2004), for Vachelia farnesiana of the tribe Acacieae, and for Mimosa setosa var. paludosa (Dahmer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome base numbers x = 6, 7, 8,9,10,11,13,15 and 16 are reported for species of the genus ( Figure 5). Hughes (1998) and Cardoso et al (2000), in their studies on the genus Leucaena, reported that the presence of different chromosome base numbers in a given taxon is related to the taxonomic differences within it and reflects the complexity of evolutionary patterns in the diploid and tetraploid races (Abou-El-Enain 2002).…”
Section: Variations Of the Chromosome Number And Ploidy Level In Genumentioning
confidence: 99%